Religion and Modern Society: Criticism of Phil Zuckerman's Ideas on Religion - Alfathoni, Waldi; Wijaya, Wijaya; Nugroho, Nugroho (Al-Adyan: Journal of Religious Studies, 2024)
Phil Zuckerman, a prominent sociologist and professor at Pitzer College, California, explores the landscape of secularism in Denmark and Sweden through his empirical research. His work, particularly highlighted in "Society Without God", examines how this society functioned without significant religious influence. Zuckerman argues that secularism fosters ethical living and societal well-being, contrasting it with the perceived negative impacts of religious influence, such as intolerance. In this research, a comprehensive exploration of Phil Zuckerman was carried out analytically and critically regarding his ideas. The method used in this research is a qualitative method, with a hermeneutical analysis approach. The data collection technique uses literature or library research. The study found that while it received praise for its optimistic picture of a secular society, Zuckerman's views were criticized for oversimplifying complex social dynamics and the broader factors that influence societal conditions beyond religious observance.Phil Zuckerman, seorang sosiolog terkemuka dan profesor di Pitzer College, California, mengeksplorasi lanskap sekularisme di Denmark dan Swedia melalui penelitian empirisnya. Karyanya, khususnya yang disorot dalam "Society Without God” mengkaji bagaimana masyarakat ini berfungsi tanpa pengaruh agama yang signifikan. Zuckerman berpendapat bahwa sekularisme mendorong kehidupan etis dan kesejahteraan masyarakat, dibandingkan dengan dampak negatif pengaruh agama, seperti intoleransi. Studi ini melakukan eksplorasi analitis dan kritis yang mendalam terhadap ide-ide Phil Zuckerman. Metode yang digunakan dalam penelitian ini adalah kualitatif, dengan pendekatan analisis hermeneutis. Teknik pengumpulan data melibatkan penelitian kepustakaan atau tinjauan pustaka. Studi ini menemukan bahwa meskipun gambaran optimis Zuckerman tentang masyarakat sekuler patut dipuji, pandangannya dikritik karena terlalu menyederhanakan dinamika sosial yang kompleks dan faktor-faktor lebih luas yang mempengaruhi kondisi masyarakat di luar ketaatan beragama.